Factors associated with diabetes complications among people with type 2 diabetes in Sabah, Malaysia: A cross-sectional study - Alif Ramli; Fredie Robinson; Mohd Hafizuddin Ahmad; Balachandar S. Sayapathi; Carol Lim Kai Joo; Syakeel Muhammad; Nirmal Kaur; Anisah Jantim; Ismail Lasa; Norimah Yusof (Via Medica, 2024)
The rising prevalence of type 2 diabetes (T2D) and diabetes complication result in substantial healthcare expenses, particularly given the considerable government subsidies provided to the healthcare system in Malaysia [1]. It is essential to periodically research diabetes complications and related variables to identify evolving trends and devise a plan of action. The objective of this study was to determine the prevalence and factors associated with diabetes complications among people with T2D in Sabah, Malaysia.